Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine the length of the third side of a triangle when two sides and the included angle are known, we can use the Law of Cosines. The Law of Cosines states:
[tex]\[ c^2 = a^2 + b^2 - 2ab \cos(C) \][/tex]
where [tex]\( c \)[/tex] is the length of the third side we need to find, [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are the lengths of the given sides, and [tex]\( C \)[/tex] is the included angle.
Given:
- [tex]\( a = 3 \)[/tex]
- [tex]\( b = 4 \)[/tex]
- [tex]\( C = 60^\circ \)[/tex]
First, we convert the angle from degrees to radians since the cosine function generally uses radians in mathematical calculations. However, we will assume we can directly use the degrees for conceptual understanding here:
Using [tex]\( C = 60^\circ \)[/tex] and knowing that [tex]\( \cos(60^\circ) = \frac{1}{2} \)[/tex]:
Let's plug in the values into the Law of Cosines formula:
[tex]\[ c^2 = 3^2 + 4^2 - 2 \cdot 3 \cdot 4 \cdot \cos(60^\circ) \][/tex]
[tex]\[ c^2 = 9 + 16 - 2 \cdot 3 \cdot 4 \cdot \frac{1}{2} \][/tex]
[tex]\[ c^2 = 9 + 16 - 12 \][/tex]
[tex]\[ c^2 = 25 - 12 \][/tex]
[tex]\[ c^2 = 13 \][/tex]
Next, we find the length of [tex]\( c \)[/tex] by taking the square root of both sides of the equation:
[tex]\[ c = \sqrt{13} \][/tex]
So, the length of the third side of the triangle is [tex]\( \sqrt{13} \)[/tex].
Therefore, the correct answer is:
C. [tex]\( \sqrt{13} \)[/tex]
[tex]\[ c^2 = a^2 + b^2 - 2ab \cos(C) \][/tex]
where [tex]\( c \)[/tex] is the length of the third side we need to find, [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are the lengths of the given sides, and [tex]\( C \)[/tex] is the included angle.
Given:
- [tex]\( a = 3 \)[/tex]
- [tex]\( b = 4 \)[/tex]
- [tex]\( C = 60^\circ \)[/tex]
First, we convert the angle from degrees to radians since the cosine function generally uses radians in mathematical calculations. However, we will assume we can directly use the degrees for conceptual understanding here:
Using [tex]\( C = 60^\circ \)[/tex] and knowing that [tex]\( \cos(60^\circ) = \frac{1}{2} \)[/tex]:
Let's plug in the values into the Law of Cosines formula:
[tex]\[ c^2 = 3^2 + 4^2 - 2 \cdot 3 \cdot 4 \cdot \cos(60^\circ) \][/tex]
[tex]\[ c^2 = 9 + 16 - 2 \cdot 3 \cdot 4 \cdot \frac{1}{2} \][/tex]
[tex]\[ c^2 = 9 + 16 - 12 \][/tex]
[tex]\[ c^2 = 25 - 12 \][/tex]
[tex]\[ c^2 = 13 \][/tex]
Next, we find the length of [tex]\( c \)[/tex] by taking the square root of both sides of the equation:
[tex]\[ c = \sqrt{13} \][/tex]
So, the length of the third side of the triangle is [tex]\( \sqrt{13} \)[/tex].
Therefore, the correct answer is:
C. [tex]\( \sqrt{13} \)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.